Latin-American guidelines for opioid use in chronic nononcologic pain (2017)
Aim: Latin-American experts in the use of opioids in patients with chronic nononcologic pain (CNOP) have updated existing recommendations to current Latin-American reality. Methods: Several key opinion leaders from Latin America participated in a face-to-face meeting in Guatemala (April 2015) to discuss the use of opioids in CNOP. Subgroups of experts worked on specific topics, reviewed the literature and shaped the final manuscript. Results: The expert panel developed guidelines taking into consideration the utility of both opioid and nonopioid analgesics and factors pertaining to their efficacy, safety, adherence, administration and risks for abuse/addiction. Conclusion: Latin-American guidelines for the use of opioids in CNOP should improve pain relief and patients' quality of life by increasing access to these effective agents.